The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1369/jhc.5a6815.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Effect of Inhibition of Aminopeptidase-A during Nephrogenesis

Abstract: Aminopeptidase-A (APA) is a metalloprotease that cleaves N-terminal aspartyl and glutamyl residues from peptides. Its best-known substrate is angiotensin II (Ang II), the most active compound of the renin-angiotensin system (RAS). The RAS is involved in renal development. Most components of the RAS system are expressed in the developing kidney. Thus far, APA has not been studied in detail. In the present study we have evaluated the expression of APA at the protein, mRNA, and enzyme activity (EA) level in the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…No study has directly explored renin activity in podocytes. Our results suggest the existence of renin activity in podocytes, as evidenced by the formation of ANG I, ANG-(1-9), ANG II, and ANG-(1-7) after cells were incubated with ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). This conversion was inhibited by a renin inhibitor, demonstrating that the formation of angiotensin peptides from ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) is, in part, attributable to renin.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…No study has directly explored renin activity in podocytes. Our results suggest the existence of renin activity in podocytes, as evidenced by the formation of ANG I, ANG-(1-9), ANG II, and ANG-(1-7) after cells were incubated with ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). This conversion was inhibited by a renin inhibitor, demonstrating that the formation of angiotensin peptides from ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) is, in part, attributable to renin.…”
Section: Discussionmentioning
confidence: 52%
“…The conversion of ANG II to ANG III was inhibited by amastatin, an aminopeptidase A inhibitor. Aminopeptidase A is a 250-kDa transmembrane protein that cleaves ANG II to ANG III (40), and ANG III is subsequently converted to ANG IV by amniopeptidase N. The expression of aminopeptidase A in podocytes has been previously reported in developing kidneys (11). Highlighting the role of aminopeptidase A in the metabolism of ANG II and glomerular injury, Dijkman et al (12) found that mice injected with antibodies against aminopeptidase A developed proteinuria.…”
Section: Discussionmentioning
confidence: 97%
“…Faint expression has also been observed in the juxtaglomerular cells, endothelial cells of the peritubular capillaries and in the pars media of the arteries (Assmann, et al, 1992;Dijkman, et al, 2006;Mentzel, et al, 1996b).…”
Section: Introductionmentioning
confidence: 94%
“…Glutamyl aminopeptidase is a small membrane bound metalloprotease that cleaves N-terminal aspartyl and glutamyl residues from peptides (Dijkman et al, 2006). Its best-known target is Angiotensin II (Ang II) a component of the angiotensin-renin system (RAS) (Cogolludo et al, 2005; Reaux et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Its best-known target is Angiotensin II (Ang II) a component of the angiotensin-renin system (RAS) (Cogolludo et al, 2005; Reaux et al, 2001). The RAS system plays a role in the regulation of blood pressure and is also important for the development of the mammalian kidney (Dijkman et al, 2006). …”
Section: Introductionmentioning
confidence: 99%